Hepatoprotective effect of botanical drug formula on high-fat diet-induced non-alcoholic fatty liver disease by inhibiting lipogenesis and promoting anti-oxidation - Ning, De-Shan; Chen, Yu-Ju; Lin, Chien-Ju; Wang, Ching-Chiung; Zhao, Hong-Wei; Wang, Kun-Teng; Lee, Ming-Chung; Tayo, Lemmuel L.; Chiu, Wan-Chun; Yeh, Chiu-Li; Lee, Chia-Jung (Frontiers in Pharmacology, 2022)
With the prevalence of obesity and other components of metabolic syndrome, Non-alcoholic fatty liver disease (NAFLD) has become increasingly common. In recent years, much attention has been paid to various plant sources, hoping to find a treatment for NAFLD in plants. The Livsooth authentic herbal formula (LAH, 樂悠本草), a botanical drug formula combined with Puerariae lobatae radix, Lonicerae japonicae flos, Hoveniae semen, and Siraitiae fructus. This study used a network pharmacology approach to predict the potential mechanisms of LAH against NAFLD. Gene Ontology (GO) and KEGG pathway enrichment analyses have identified potential biochemical and signaling pathways. Subsequently, the potential mechanism of action of LAH on NAFLD predicted by network pharmacology analysis was validated in a high-fat diet (HFD)-induced NAFLD model in C57BL/6 mice. Our results demonstrated that LAH ameliorated hepatocyte steatosis in liver tissue by activating the AMPK pathway and decreasing serum triglycerides, low-density lipoprotein, glucose, and cholesterol. Besides, LAH increased the hepatic antioxidant enzymes activities, suggested that LAH improved oxidative stress markers in HFD induced NAFLD mice. In vitro experiments confirmed that the active component of LAH, puerarin, regulates lipid accumulation through the AMPK pathway. In conclusion, our study shows that network pharmacology predictions are consistent with experimental validation. LAH can be a candidate supplement for the prevention of NAFLD.